Уравнения мгновенных и интегральных мощностей несинусоидальных 3–фазных процессов - Сиротин, Ю.А.; Иерусалимова, Т.С. (Електротехніка і електромеханіка, 2016)
Для 3-фазной схемы электроснабжения рассмотрены несинусоидальные режимы, классифицируемые скалярной и
векторной мгновенными мощностями (ММ). В рамках временного и спектрального подходов теории мощности получены комплексные формы активной (скалярной) ММ и (неактивной) векторной ММ. Для 4-проводной сети получены
уравнения мощности комплексных скалярных и комплексных векторных мощностей несинусоидальных режимов.
Уравнения мощностей обобщают соответствующие уравнения синусоидальных несимметричных режимов
в 4-проводной сети. Для 3-фазної схеми електропостачання розглянути несинусоїдальні режими, що класифікуються скалярною та векторною
миттєвими потужностями (МП). В рамках часового та спектрального підходів теорії потужності отримані комплексні
форми активної (скалярної) МП і (неактивній) векторної МП. Для 4-провідної мережі отримані рівняння потужності комплексних скалярних і комплексних векторних потужностей несинусоїдальних режимів. Рівняння потужностей узагальнюють відповідні рівняння синусоїдальних несиметричних режимів у 4-провідної мережі. Purpose. To identify the mathematical relationship between the
instantaneous powers (classical and vectorial) and integral
powers in non-sinusoidal mode and to get complex form of instantaneous powers in 3-phase 4-wire power supply in terms of
the spectral approach. Methodology. We have applied the vector approach with one voice allows you to analyze the energy
characteristics of 3-phase power supply circuits (for 4-wire and
3-wire circuits) in sinusoidal and non–sinusoidal mode, both the
time domain and frequency domain. We have used 3-
dimensional representation of the energy waveforms with the
complex multi-dimensional Fourier series. Results. For 4-wire
network with a non-sinusoidal (regardless of their symmetry)
processes, we have developed the mathematical model onedimensional representations of the complex form for the active
(scalar) instantaneous power (IP) and 3-dimensional form (inactive) vectorial IP. It is possible to obtain two dual integral
power equations for complex scalar and vector integrated
power of non-sinusoidal modes. The power equations generalize
generalizes the equations of sinusoidal modes for 4-wire network. Originality. In addition to the classification of energy
local regimes in the time domain for the first time we spent the
classification of non-sinusoidal modes in the spectral region and
showed the value and importance of the classification of regimes
based on the instantaneous powers. Practical value. The practical value the obtained equations is the possibility of their use for
improving the quality of electricity supply and the quality electricity consumption.